2007
DOI: 10.1645/ge-1110r.1
|View full text |Cite
|
Sign up to set email alerts
|

Human Neurocysticercosis: Rightward Hemisphere Asymmetry in the Cerebral Distribution of a Single Cysticercus

Abstract: The distribution of single cysticerci between cerebral hemispheres was studied in 227 adult cases of calcified and vesicular neurocysticercosis (NC). A rightward lateralization of calcified cysticerci was significant only in women, whereas vesicular cysticerci were equally distributed in both hemispheres. Factors related with the differences in the inflammatory response and in the regional cerebral blood flow between genders could be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The number of transitional cysts was 1·8‐fold higher in female patients than in male, and this gender effect was not only statistically significant ( P = 0·002) but also constant over time . In one study evaluating single parasite infections in a series of patients, calcified parasites were significantly more frequent in women than in men . With regard to CSF characteristics, it was also demonstrated that CSF cellularity was higher in women than in men .…”
Section: Inflammation and Host Factorsmentioning
confidence: 98%
“…The number of transitional cysts was 1·8‐fold higher in female patients than in male, and this gender effect was not only statistically significant ( P = 0·002) but also constant over time . In one study evaluating single parasite infections in a series of patients, calcified parasites were significantly more frequent in women than in men . With regard to CSF characteristics, it was also demonstrated that CSF cellularity was higher in women than in men .…”
Section: Inflammation and Host Factorsmentioning
confidence: 98%
“…In relation to seizure recurrence, only two studies with contradictory results were included in the metaanalysis, one showing no differences between the 2 groups of patients, and the other showing a reduction in the number of generalized seizures in the albendazole group [104,105]. Host factors, such as gender and age, CNS lateralization of cysticerci as well as cysticidal treatment could be involved in parasite calcification or disappearance [105,109,110]. One factor that proved to be involved in seizure recurrence is the persistence of calcification after parasite death [84,106,107].…”
Section: Located In Parenchyma or In The Sa Space Of The Convexitymentioning
confidence: 99%